Combining good mechanical properties and high translucency in yttrium-doped ZrO2-SiO2 nanocrystalline glass-ceramics. Issue 1 (January 2022) - Liu, Yang; Yang, Dangguo; Riekehr, Lars; Engqvist, Håkan; Fu, Le; Xia, Wei
Abstract: It is challenging to develop a material that combines good mechanical properties and high translucency since these properties are generally not coincident in one material. In this study, we prepared ZrO2 -SiO2 nanocrystalline glass-ceramics that combines the above two types of properties. Raw powder with 55 mol%, 65 mol%, and 75 mol% ZrO2 and each with 5 mol% yttrium as a dopant was prepared by sol-gel method, followed by spark plasma sintering to obtain dense glass-ceramics. XRD results demonstrated that the glass-ceramics with 65 mol% and 75 mol% ZrO2 were composed of tetragonal-ZrO2, whereas, that with 55 mol% ZrO2 was composed of cubic-ZrO2 . The as-sintered glass-ceramics showed black/brown discoloration, but they obtained high translucency after thermal treatment. X-ray energy-dispersive spectrometry (EDS) results in scanning electron transmission microscopy (STEM) mode demonstrated yttrium dopants were predominately distributed in ZrO2 nanocrystallites. The glass-ceramics with 65 mol% ZrO2 had the highest flexural strength, achieving an average value of 673 MPa. The glass-ceramics with different compositions sintered at different temperatures showed fracture toughness values ranging from 5.25 MPa m 1/2 to 6.69 MPa m 1/2 . The strong and translucent ZrO2 -SiO2 nanocrystalline glass-ceramics showing great protentional to be used in many fields.